KEPADATAN DAN DISTRIBUSI BIVALVIA PADA MANGROVE DI PANTAI CERMIN KABUPATEN SERDANG BEDAGAI PROVINSI SUMATRA UTARA - Suwondo '; Elya Febrita; Nurida Siregar (Program Studi Pendidikan Biologi, 2012)
The study was conducted to determine the density and distribution of mangroves in Coastal Bivalvia in Pantai Cermin Bedagai Serdang, Sumatra Utara Province, in January to February 2012. The study used survey methods, field data collection using a plot that is placed on a transect. Determination of observation stations done purposively sampling at three observation stations in the area intertidial. The data were analyzed descriptively. The results showed that four types Bivalvia found that Anadara sp, Pharus sp, sp Geloina and Perna viridis. The highest density found in the type Pharus sp with a mean density of 2.75 indv/m3. The lowest densities found on the type of Anadara sp with a rate of 2.07 indv/m3. Bivalvia distribution patterns on patterns of uneven distribution.Keywords: Bivalvia, Density Distribution.